Comparative evaluation of the efficacy of two controlled release devices: Chlorhexidine chips and indigenous curcumin based collagen as local drug delivery systems - Sruthima N. V. S. Gottumukkala; Sabitha Sudarshan; Satyanarayana Raju Mantena (Wolters Kluwer Medknow Publications, 2014)
Aim: To comparatively evaluate the therapeutic efficacy of chlorhexidine (CHX) chips (Periocol-CG) and indigenous curcumin (CU) based collagen as adjuncts to scaling and root planning in the nonsurgical management of chronic periodontitis. Materials and Methods: A total of 120 sites from 60 patients presenting with chronic periodontitis (age group 25-55 years) of both sexes, with pocket depth of ≥5 mm with radiographic evidence of bilateral bone loss were earmarked for the study. A split mouth design was employed, and all the clinical parameters-plaque index, gingival index, probing pocket depth (PPD) and clinical attachment levels (CAL) were recorded at baseline, 1 month, 3 months, and 6 months. However, the microbiological parameters, i.e., N-benzoyl-DL-arginine-β-naphthylamide (BANA) test and microbial colony count were recorded at baseline, 3 months and 6 months postoperatively. Results: Significant reduction in plaque and gingival index scores were observed in both groups at the end of the study period, i.e., 6 months. The microbiological parameters (BANA test, microbial colony count), PPD and CAL levels also showed significant improvement in both groups. However, at the end of the study period CHX group showed greater improvement in all of these parameters compared to CU collagen group. Conclusion: Future directions of this study should include targeting the beneficial effects of these local drug delivery systems at varied concentrations so that they could be utilized to achieve the maximum beneficial therapeutic effects in the nonsurgical treatment of periodontal disease.